Polymorphism of sheep POU1F1 gene exon 6 and 3'UTR region and their association with milk production traits - Ozmen, O.; Kul, S.; Unal, E.O. (Shiraz University, 2014)
The purpose of the study was to detect the AluI and DdeI polymorphisms within POU1F1 gene exon 6 and 3'UTR region in Turkish sheep breeds, and their association with milk productive traits. Jugular blood samples were collected from 50 Sakiz, 50 White Karaman, and 50 Awassi sheep using EDTA as an anticoagulant. PCR-RFLP and sequencing analysis were performed to investigate possible polymorphisms in the exon 6 and 3' flanking region of the sheep POU1F1 gene. The PCR products were digested with restriction endonuclease AluI and DdeI, and biallelic polymorphism was found with restriction endonuclease AluI and two genotypes (TT (296 bp and 173 bp) and CC (235 bp, 173 bp and 61 bp)) were detected. White Karaman and Awassi breeds did not show polymorphisms for AluI restriction sites. No polymorphism at the DdeI cleavage sites was detected in the three sheep breeds. Significant statistical results were found in milk yield (***P<0.001), fat (**** P<0.001) and lactose (*P<0.05) values with TT and CC genotypes, however no significant association of TT and CC genotypes with protein values was detected (P>0.05) and individuals with genotype TT had a superior milk yield in Sakiz sheep breeds. As sequence results, seven variation points were determined for exon 6 (g.185T>C) and 3'UTR (g.220G>A, g.229C>T, g.248C>T, g.250A>T, g.255T>C, g.258C>T) of the sheep POU1F1 gene. We have reported here for the first time single nucleotide polymorphisms of the POU1F1 gene for both exon 6 and 3'UTR and its effects on milk traits in Turkish sheep breeds were evaluated.
Keywords: Milk traits; Polymorphism; POU1F1 gene; Turkish sheep breeds